Seismic Behavior Factors of Steel Frames Braced with Viscoelastic Damping System - Alagawani, Besan; Alqaryouti, Yousef Harb (Journal of Engineering and Technological Sciences, 2016)
In this study a number of seismic behavior factors (overall ductility, response modification, and overstrength) of ordinary moment steel frames with viscoelastic bracing system were evaluated. These factors are not provided for ordinary moment steel frames with viscoelastic bracing system in building seismic codes such as the International Building Code (IBC) or Euro Code (EN). Moreover, similar frames without viscoelastic bracing were assessed and compared as well. A linear history analysis both two types with a different number of stories and span lengths was carried out using different earthquake records, which were selected to include variability in ground motion characteristics. Pushover analysis was then performed after defining the sizes of the elements and assigning material nonlinearity to the discrete hinge where plastic rotation occurs to beams and columns according to FEMA 356. Such analysis allows evaluating the overall ductility and the overstrength of each building of concern by using the yield and ultimate displacements and base shear forces obtained from the pushover curve. The results showed that overall ductility, overstrength, and response modification decreased with an increase of the number of stories for all buildings or when the bay length increased. Adding viscoelastic dampers increased the seismic behavior factors for all buildings significantly.